Parasitism of autumnal morphs of the soybean aphid (Hemiptera: Aphididae) by Binodoxys communis (Hymenoptera: Braconidae) on Buckthorn - Asplen, Mark K.; Wyckhuys, Kris A.G.; Heimpel, George E. (Oxford University Press, 2011)
The soybean aphid, Aphis glycines Matsumura (Hemiptera: Aphididae), is both heteroecious and holocyclic, seasonally alternating between buckthorn (Rhamnus spp.), (the primary, overwintering host) and soybean, Glycine max (L.) Merr. (the secondary host). Recently, a classical biological control program for this invasive pest has been implemented in North America using the Asian aphidiine braconid wasp Binodoxys communis Gahan. Two critical, related questions regarding the overwintering biology of B. communis are 1) does the parasitoid maintain fidelity to A. glycines throughout the aphid life cycle and follow it to its primary host; and, if it does, 2) is parasitoid migration facilitated by phoretic movement within buckthorn-specific winged aphids? In the laboratory, we compared B. communis parasitism on several different autumnal morphs of A. glycines: winged gynoparae (fall migrants) and their oviparous offspring on buckthorn, fourth-instar alatoid nymphs that would form either gynoparae or summer migrants on soybean, and third-instar gynoparous alatoid nymphs on soybean. We also introduced gynoparae and B. communis onto caged buckthorn plants in southeastern Minnesota to examine autumnal parasitism under natural conditions. In both the laboratory and field, parasitism rates of oviparae were much higher than those of gynoparae. In addition, B. communis rarely completed development on fourth-instar alatoid nymphs. Although wasps successfully developed on third-instar gynoparous nymphs, these hosts mummified before forming wings. These results suggest that although at least one buckthorn-specific morph of A. glycines seems suitable for B. communis parasitism, it is unlikely that alate-mediated dispersal of immature parasitoids is an adaptive strategy to locate Rhamnus in this species.